Measuring the complexity of general practice consultations: a Delphi and cross-sectional study in English primary care - Salisbury, Chris (Br J Gen Pract, 2021)
BACKGROUND: The complexity of general practice consultations may be increasing and varies in different settings. A measure of complexity is required to test these hypotheses. AIM: To develop a valid measure of general practice consultation complexity applicable to routine medical records. DESIGN AND SETTING: Delphi study to select potential indicators of complexity followed by a cross-sectional study in English general practices to develop and validate a complexity measure. METHOD: The online Delphi study over two rounds identified potential indicators of consultation complexity. The cross-sectional study used an age–sex stratified random sample of patients and general practice face-to-face consultations from 2013/2014 in the Clinical Practice Research Datalink. The authors explored independent relationships between each indicator and consultation duration using mixed-effects regression models, and revalidated findings using data from 2017/2018. The proportion of complex consultations in different age–sex groups was assessed. RESULTS: A total of 32 GPs participated in the Delphi study. The Delphi panel endorsed 34 of 45 possible complexity indicators after two rounds. After excluding factors because of low prevalence or confounding, 17 indicators were retained in the cross-sectional study. The study used data from 173 130 patients and 725 616 face-to-face GP consultations. On defining complexity as the presence of any of these 17 factors, 308 370 consultations (42.5%) were found to be complex. Mean duration of complex consultations was 10.49 minutes, compared to 9.64 minutes for non-complex consultations. The proportion of complex consultations was similar in males and females but increased with age. CONCLUSION: The present consultation complexity measure has face and construct validity. It may be useful for research, management and policy, and for informing decisions about the range of resources needed in different practices.